Determination and Evaluation of Sense of Coherence in Women in Semi-urban Nepal: A part of the Heart-health Associated Research, Dissemination, and Intervention in the Community (HARDIC) Trial - Thapa, D. R.; Oli, N.; Vaidya, A.; Suominen, S.; Ekström-Bergström, A.; Areskoug Josefsson, K.; Krettek, A. (Kathmandu University Medical Journal, 2022)
Background Sense of coherence (SOC) is a core concept of salutogenesis which relates to individuals’ overall life orientation. Stronger SOC associates with better coping strategies, better health, and better quality of life. Although the SOC-questionnaire is validated in many cultures and languages, it has not, to date, been applied in Nepal. Objective To determine and evaluate women’s SOC before and after a health education intervention. Method This study was conducted as a part of the Heart-health Associated Research, Dissemination, and Intervention in the Community in the semi-urban Jhaukhel- Duwakot Health Demographic Surveillance Site in Nepal. Jhaukhel and Duwakot were selected as the control and intervention areas, respectively. Participants were women with children aged 1-7 years. Eight hundred and fifty-seven women before and 1,268 women after the health education intervention participated in the study. The statistical analysis was carried out with chi-square tests and one-way uni-variate ANOVA. Result Women’s total SOC mean values at baseline were 51.1-57.4 and at follow up 54.4-54.9 in the intervention and control area, respectively. At baseline, SOC was significantly weaker in the intervention area compared to the control area (p < 0.001). At follow-up three months later, SOC was significantly stronger in the intervention area than in the control area (p < 0.001). Conclusion Nepalese women had weaker SOC than women in high-income countries, but comparable to neighboring country India with similar cultural features. Empowerment of women through community participation and health education strengthened SOC. The SOC-13-questionnaire in its Nepali version is recommended to be further evaluated.